Implementasi Perancangan Komunikasi Visual Media Iklan Pada Brand Dua Salak UMKM KWT Muda Jaya Sleman - Hukubun, Lejar Daniartana; Hadapiningrani, R; Hilmi N, Anhar; Pratama, Gregorius (DHARMA BAKTI, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are businesses undertaken by several individuals to sell their respective goods. The types and forms of these enterprises vary, encompassing clothing, food, goods, and services. One example of an MSME in Sleman is the production of chips from salak fruit, where the original fruit is processed into a snack without preservatives because its taste is already sweet, akin to the original fruit. To promote these MSME products and strengthen their branding, efforts are made in designing visual communication through advertising media. Advertising media design and the SWOT method are employed to produce advertising media that are appropriate, accurate, and communicative according to the target audience, thereby enhancing the visibility and positive progress of MSMEs in Sleman.